Peripheral shift in the viable chondrocyte population of the medial femoral condyle after anterior cruciate ligament injury in the porcine knee. - Meggin Q Costa; Martha M Murray; Jakob T Sieker; Naga Padmini Karamchedu; Benedikt L Proffen; Braden C Fleming (PLoS ONE, 2021)
Anterior cruciate ligament injuries result in posttraumatic osteoarthritis in the medial compartment of the knee, even after surgical treatment. How the chondrocyte distribution within the articular cartilage changes early in this process is currently unknown. The study objective was to investigate the chondrocyte distribution within the medial femoral condyle after an anterior cruciate ligament transection in a preclinical model. Forty-two adolescent Yucatan minipigs were allocated to receive unilateral anterior cruciate ligament surgery (n = 36) or no surgery (n = 6). Central coronal sections of the medial femoral condyle were obtained at 1- and 4 weeks after surgery, and the chondrocyte distribution was measured via whole slide imaging and a cell counting batch processing tool utilized in ImageJ. Ki-67 immunohistochemistry was performed to identify proliferating cells. Empty lacunae, karyolysis, karyorrhexis, and pyknosis were used to identify areas of irreversible cell injury. The mean area of irreversible cell injury was 0% in the intact controls, 13.4% (95% confidence interval: 6.4, 20.3) at 1-week post-injury and 19.3% (9.7, 28.9) at 4 weeks post-injury (p < .015). These areas occurred closest to the femoral intra-articular notch. The remaining areas containing viable chondrocytes had Ki-67-positive cells (p < .02) and increased cell density in the middle (p < .03) and deep zones (p = .001). For the entire section, the total chondrocyte number did not change significantly post-operatively; however, the density of cells in the peripheral regions of the medial femoral condyle increased significantly at 1- and 4 weeks post-injury relative to the intact control groups (p = .032 and .004, respectively). These data demonstrate a peripheral shift in the viable chondrocyte population of the medial femoral condyle after anterior cruciate ligament injury and further suggest that chondrocytes with the capacity to proliferate are not confined to one particular cartilage layer.